Peningkatkan Kesadaran Halal Lifestyle di Kalangan Santriwati Pondok Pesantren Putri Al-Barqy - Faza, Aghnia Nadia; Aqila, Meiza; Nissa, Fadia Khoirun; Widodo, Deswita Putri; Orrero, Geren Aurelia (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2025)
This community service activity aims to increase the awareness and understanding of santriwati Pesantren Putri Al-Barqy towards the importance of implementing a halal lifestyle in everyday life. Halal lifestyle does not only include aspects of food and beverages, but also includes clothing, cosmetics, financial transactions, and media consumption in accordance with the principles of Islamic law. The methods used include initial observation, distribution of pre-test and post-test questionnaires, interactive counseling, and comprehensive evaluation. The initial survey results show that most students still have a limited understanding of the concept of halal comprehensively. After the activity was carried out, the post-test results showed a significant increase in participants' knowledge, awareness, and desire to implement a halal lifestyle. Educational media in the form of brochures and open discussions proved effective in delivering material and building personal reflection. As a form of desire, the service team compiled a digital module that can be accessed independently by santriwati, and encouraged the integration of the material into the routine curriculum of the Islamic boarding school. This activity makes a real contribution in instilling halal values as part of the identity and habits of santriwati, and encourages them to become agents of change who can spread halal lifestyles in society.